SUMUR RESAPAN AIR HUJAN UNTUK PENCEGAHAN BANJIR GENANGAN DI SMA NEGERI UNGGUL ACEH TIMUR - Neneng Mardiah Bukit, Ipak; Masthura, Lely; Fahriana, Nina; Salsabila, Shafira; Husein Nst, Said; Akbar Ashafy, Alief (Fakultas Teknik, Universitas Samudra, 2025)
SMA Negeri Unggul Aceh Timur is located on uneven and contoured land with cohesive soil types such as clay and loam. During the rainy season, the school will experience waterlogging that lasts quite a long time. This happens because rainwater does not immediately seep into the ground because the nature of fine-grained cohesive soil tends to have dense particles. For soil conditions like this, it is necessary to make holes to collect rainwater runoff so that it will seep into the ground more quickly, called Rainwater Infiltration Wells (SRAH). The Community Service Activity (PKM) carried out by Lecturers at the Faculty of Science and Technology, Samudra University aims to provide solutions to schools anticipating the occurrence of rainwater inundation thats building rainwater infiltration wells (SRAH). The process of implementing the activity went well and school residents were able to understand the function of rainwater infiltration wells. However, for a fairly large area such as SMA Negeri Unggul Aceh Timur, more infiltration wells are needed to accommodate the water puddles that occur after rain